Development of a Copro-RPA-CRISPR/Cas12a assay to detect Echinococcus granulosus nucleic acids isolated from canine feces using NaOH-based DNA extraction method. - Guoqing Shao; Xiaowei Zhu; Ruiqi Hua; Yanxin Chen; Guangyou Yang (PLoS Neglected Tropical Diseases)
Background Cystic echinococcosis (CE), caused by Echinococcus granulosus sensu lato (E. granulosus s.l.), remains a significant zoonotic parasitic disease affecting both livestock and humans. It arises from the ingestion of food and water contaminated with canine feces containing E. granulosus eggs. The detection of these eggs in canine feces is essential for guiding effective preventative measures against the disease. Therefore, the development of a novel accurate, rapid, and visually interpretable point-of-care test is crucial for controlling CE. Methods We combined recombinase polymerase amplification (RPA) and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) with a CRISPR-associated protein 12a (Cas12a) system, forming the RPA-CRISPR/Cas12a assay. This assay targeted the E. granulosus mitochondrial nad2 gene and utilized a lateral flow strip for visual readout. To improve field applicability, we integrated a simple and cost-effective NaOH-Based DNA extraction method. Clinical validation included testing DNA extracted from eighteen canine fecal samples, followed by comparison with quantitative PCR (qPCR) and two commercial enzyme-linked immunosorbent assay (ELISA) kits. Results The RPA-CRISPR/Cas12a assay showed a detection limit of 1 fg/μL DNA, without any cross-reactivity with related tapeworms such as Echinococcus multilocularis, Dipylidium caninum, Taenia hydatigera, Taenia multiceps, and Taenia pisiformis. When applied to 62 clinical fecal samples from dogs, the RPA-CRISPR/Cas12a assay demonstrated 68% sensitivity, while the developed RPA-CRISPR/Cas12a-NaOH assay exhibited 45% sensitivity. In the field performance comparison of the RPA-CRISPR/Cas12a and the RPA-CRISPR/Cas12a-NaOH assay with qPCR and two ELISA kits, the sensitivity, consistency rate, and Youden's index suggested good or fair agreement with the currently employed detection methods. Conclusion This study describes the development and validation of the RPA-CRISPR/Cas12a and RPA-CRISPR/Cas12a-NaOH assays for detecting E. granulosus in canine feces. The developed assays surpassed previous detection methods in providing enhanced diagnostic sensitivity and enabling point-of-care testing. Moreover, these assays hold potential for surveilling E. granulosus in low-income countries.